Pertentangan Materiil antara Undang-Undang Nomor 7 Tahun 2021 dengan Peraturan Pemerintah Nomor 49 Tahun 2022 Terhadap PPN atas Emas Batangan - Munthe, Herbert A.S; Karim, Moh. (Neolectura, 2023)
The preparation of statutory regulations should follow established principles and norms. However, sometimes the government tends to ignore these principles, especially for reasons of development and community welfare. This article examines the conformity of Government Regulation Number 49 of 2022 with the principles and norms for the formation of statutory regulations. One of the contents of this regulation is to provide facilities for non-collection of taxes owed on imports and deliveries of gold bullion which are not for the purposes of foreign exchange reserves. Basically, these facilities aim to support the availability of certain goods and services that are strategic for national development, especially basic needs for the community. Based on normative legal research using a statutory and conceptual approach, it can be concluded that Government Regulation Number 49 of 2022 is considered to violate the authority mandated by Article 16B of the VAT Cluster Law on Harmonization of Tax Regulations.